2005
DOI: 10.1590/s0103-90162005000500013
|View full text |Cite
|
Sign up to set email alerts
|

Hanging the beef carcass by the forequarter to improve tenderness of the Longissimus dorsi and Biceps femoris muscles

Abstract: Hanging beef carcasses in different configurations in the cooler affect some carcass muscle tenderness. Forty Nellore steer carcasses (ten per day) were chosen at random in a federally inspected slaughter plant and hanged alternate left and right sides either in the traditional way by the hindquarter (HQ) or by the forequarter (FQ) also called "tenderbife". Carcasses were selected from steers up to 30 months old and had an average hot carcass weight of 244.1 kg. These carcasses were chilled for 48 hours, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…Luchiari Filho et al (2005), when evaluating the method of carcass hanging by the tendon of the gastrocnemius of the special rear limb and by the radial carpus of the forelimb of Nelore calves, did not observe any difference in the value of meat pH for the different methods of carcass hanging, what it is in agreement with the results obtained in this study (Table 1). Oliveira et al (2004), when evaluating the quality of meat from Santa Inês lambs, found the same meat pH values obtained in this study.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Luchiari Filho et al (2005), when evaluating the method of carcass hanging by the tendon of the gastrocnemius of the special rear limb and by the radial carpus of the forelimb of Nelore calves, did not observe any difference in the value of meat pH for the different methods of carcass hanging, what it is in agreement with the results obtained in this study (Table 1). Oliveira et al (2004), when evaluating the quality of meat from Santa Inês lambs, found the same meat pH values obtained in this study.…”
Section: Resultssupporting
confidence: 91%
“…Luchiari Filho et al (2005), when evaluating bovine carcasses hanged by different methods, did not verify statistical differences among hanging methods for the percentages of meat total losses in cooking. Silva (2005) also did not find differences for values of losses by cooking of bovine meat proceeding from different methods of carcass hanging (tendon of the gastrocnemius, horizontal and radial carpus).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Consumer palatability toward beef is generally attributed to tenderness, flavor, and/or juiciness 1 . The primary beef qualities are improved by post-mortem aging due to proteolysis within the muscle tissue structures, such as myofibrillar proteins, over time 14 . Beef metabolites are changed during aging, e.g., amino acid production by proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…A força de cisalhamento, também não foi influenciada pelo método de suspensão ou pelo sexo dos animais (P>0,05), diferentemente do encontrado porLuchiari Filho et al (2005) que trabalhando com suspensão tradicional e suspensão pelo carpo radial encontraram valores de força de cisalhamento de 4,78 Kg e 3,53Kg respectivamente para os métodos de suspensão de carcaças sendo significativamente diferentes. De acordo comShackelford et al (1991) a carne bovina é considerada macia, quando os valores de força de cisalhamento são Entretanto observa-se uma variação individual muito grande que pode ser atribuída as alterações bioquímicas que ocorrem no músculo durante a fase post mortem.…”
unclassified